Political budget cycles in European public procurement - Annika Havlik (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper studies whether political budget cycles occur in public procurement in the European Union. Using project- level data from Tenders Electronic Daily (2008-2018), I analyze different steps along the procurement process, namely the publication of the contract notice, the awarding of the contract, and the completion of the project. While there is no evidence of an increased activity in project completions, I find an increase in public procurement contract notices and awards prior to national parliamentary elections. This effect is more pronounced for visible and labor-intensive projects and can be interpreted as a "credible election promise", as the budget for the project is only committed at the time of the award and not spent yet.
Keywords: D72; D73; H57; 330; public procurement; political budget cycles; elections; European Union